Danqi Pill Protects Against Heart Failure Post-Acute Myocardial Infarction via HIF-1α/PGC-1α Mediated Glucose Metabolism Pathway - Zhang, Qian; Guo, Dongqing; Wang, Yuanyuan; Wang, Xiaoping; Wang, Qiyan; Wu, Yan; Li, Chun; Wang, Wei; Wang, Yong (Frontiers in Pharmacology, 2020)
Aim: Glucose metabolism disorder has been implicated in the pathogenesis of heart failure (HF), exacerbating cardiomyocytes injury and cardiac dyfunction in acute myocardial infarction (AMI). Danqi pill (DQP) is included in the 2015 national pharmacopoeia and widely applied in the treatment of HF in clinics in China. The aim of this study was to elucidate whether DQP acted on glucose metabolism to protect against HF post-AMI via hypoxia inducible factor-1 alpha (HIF-1α)/ peroxisome proliferator-activated receptor gamma co-activator (PGC-1α) signalling pathway. Materials and Methods: In this study, model of HF post-AMI was established by ligation of left anterior descending (LAD) artery on Sprague-Dawley (SD) rats. 28 days after treatments, cardiac functions and morphology were detected by echocardiography and HE staining. Glucose metabolism level was assesed by F-18 fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT). Expressions of HIF-1α, PGC-1α, pyruvate kinase M2 (PKM2), nuclear respiratory factor 1 (NRF1) and transcription factor A mitochondrial (TFAM) were measured by western blotting. In vitro, oxygen-glucose deprivation-reperfusion (OGD/R)-induced H9C2 injury model was used to investigate the mechanism of DQP on HIF-1α/PGC-1α signalling pathway. Results: DQP treatment protected the heart against ischemic damage as evidenced by improved functional recovery and attenuated inflammatory infiltration. Level of myocardial adenosine triphosphate (ATP) in DQP group was also up-regulated compared to that in the model group. The expressions of critical proteins involved in glucose intake and transportation such as GLUT4 and PKM2 were up-regulated, while negative regulatory proteins involved in oxidative phosphorylation were decreased in the DQP group compared to those in the model group. Impressively, DQP could up-regulate NRF1 and TFAM and promote mitochondrial biogenesis. Further study HIF-1α siRNA significantly compromised the protective effects of DQP, suggesting that the HIF-1α signaling pathway was the potential targets of DQP on HF post-AMI. Conclusion: DQP has the efficacy to improve myocardial glucose intake, mitochondrial oxidative phosphorylation and biogenesis by regulating HIF-1α/PGC-1α signalling pathway in HF post-AMI rats.